Comment on: "Centers of quasi-homogeneous polynomial planar systems" [Nonlinear Anal. RWA 13 (2012) 419]. (October 2017) - Rahimabadi, A.; Taghirad, H.D.
Abstract: We describe a counter-example which shows that ( 2 ) of theorem ( 11 ) in Algaba et al. (2012) is not correct. This part of the theorem, pinpoints whether the origin of quasi-homogeneous system ( 15 ) in Algaba et al. (2012) is a center or not. It is shown in this note that the given necessary and sufficient conditions of theorem ( 11 ), in Algaba et al. (2012) are not complete.